PENDEKATAN EFEKTIF UNTUK MENINGKATKAN KUALITAS HUBUNGAN SUAMI ISTRI - Ira Septi Sulistiana (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This study aims to explore effective approaches to enhance the quality of marital relationships between husband and wife. Employing a qualitative methodology through a library research design, this research critically analyzes scholarly works, journals, and theoretical perspectives concerning marital harmony and relationship-building strategies. The study identifies four major approaches: emotional, spiritual, psychological, and practical. The emotional approach highlights the role of empathy, emotional regulation, and open communication in strengthening emotional bonds. The spiritual approach emphasizes the significance of religious values, moral awareness, and shared spiritual practices in fostering mutual commitment and moral responsibility. The psychological approach focuses on the understanding of personality traits, emotional intelligence, and past life experiences that influence the dynamics of marriage. Meanwhile, the practical approach underlines the importance of shared daily activities and positive routines, such as household collaboration, planning, and spending meaningful time together. These activities build emotional closeness and reinforce a sense of partnership. The results of the analysis show that these four approaches are interconnected and can be integrated holistically to improve the overall quality of marital relationships. When applied consistently, they contribute to a stable, loving, and purposeful family life. This study is expected to serve as a reference for couples, counselors, and academics in the field of family and marriage development.